Language Learning Strategies Adopted by Tribal Learners - Nazar, Afia; Alamelu, C. (International Journal of Psychosocial Rehabilitation, 2020)
It is of great importance in language learning research to analyse language learning strategies. It has been explored by many over the years and given different definitions and classifications. Language learning strategies, as defined by Griffiths, are actions chosen by learners to regulate their learning [5]. According to Oxford, language learning strategies are classified as direct and indirect strategies. Direct strategy includes memory, cognitive and compensation strategy and Indirect strategy includes social, affective and metacognitive. The strategies adopted by the learners differ due to various sociological and psychological factors.Many qualitative and quantitative types of research are carried out to identify the language learning strategies of learners of different communities. Tribes are indigenous communities who are quite reluctant to adapt to changes, so this has got an impact on the language learning strategies they use. The present paper explores the language learning strategies that are adopted by the tribal learners of Attapadi area of Palakkad district to enhance their language learning ability.